EFEKTIVITAS TABLET Fe DAN SAYUR BAYAM MERAH TERHADAP PENINGKATAN KADAR HEMOGLOBIN PADA IBU HAMIL DENGAN ANEMIA DI PUSKESMAS KASANG PUDAK - Putri Dewi Anggraini (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Data from the World Health Organization (WHO) for 2018 stated that 41.8% of the causes of maternal death in developing countries were related to anemia in pregnancy. The highest prevalence of anemia in pregnant women was in West Africa reaching 59%, and the lowest anemia was in the North American country, namely the Republic of Guatemala with a prevalence reaching 12.7%, while the prevalence of anemia in Indonesia reached 44.2%. Prevalence in Indonesia is in the middle order below West Africa and above Guatemala (WHO, 2019). Riskesdas 2018, there were 38.2% of pregnant women with anemia, namely pregnant women with hemoglobin levels of less than 11.0 gram/dl. Data from the World Health Organization (WHO) for 2018 stated that 41.8%. This type of research uses Quasy Experiment with a quantitative approach to the one group research design pretest – posttest design. The population in this study were pregnant women with anemia in the Kasang Pudak Health Center area. The sample in this study amounted to 30 people. Sampling technique with Purposive Sampling. The time of the study was in December 2022. The hemoglobin level of pregnant women at the Kasang Pudak Health Center before being given Fe tablets and red spinach vegetables were mostly in the mild anemia category. Fe tablets and red spinach are effective in increasing hemoglobin levels of pregnant women at the Kasang Pudak Health Center. It is hoped that the puskesmas, especially midwives, in providing care to pregnant women with anemia can provide red spinach juice as an alternative to preventing anemia in pregnant women and by continuing to provide Fe tablets once a day as the program has been launched by the government.